MENYOAL RADIKALISME DI MEDIA DIGITAL - Ahmad Zamzamy (Institut Agama Islam Syarifuddin Lumajang, 2019)
Currently, Information and communication technology, especially internet system, have been developing very rapidly. Such developments have certainly positive and negative impacts. In the development of the digital age today, phenomenon of radicalism is increasingly established in Indonesia and the world. There have been many studies on this. Radicalism is also campaigned by internet media which eventually step into people’s life. This issue should be observed properly. Key Words: Radicalism, Digital Media, Youth Generation